A new species and new record of the genus Pexicopia (Lepidoptera: Gelechiidae) feeding on Abutilon indicum from India - Varnitha, H. N.; Hanchinal, S. G.; Shashank, P. R.; Prabhuraj, A.; Bheemanna, M.; Nidagundi, J. M. (Zootaxa, 2023)
A new species, Pexicopia tungabhadrai sp. nov. (Lepidoptera: Gelechiidae), feeding on Abutilon indicum is described from Karnataka, India. Also, this is the first report of the genus Pexicopia Common, 1958 from India. Images of adult moths, male and female genitalia and immature stages are provided.